Bible of sculpting techniques : an illustrated guide for beginners - Brown, Claire Waite (A. & C. Black, 2007)
"This is a complete step-by-step guide to techniques for sculpting in a wide range of media..... Discover how to create a variety of surface effects and finishes, and apply your skills to creative projects ranging from heads and figures to animals, landscapes and abstracts"-- Back cover.